THE ANALYSIS OF STUDENTS’ ANXIETY IN SPEAKING ENGLISH - Renita Renita; Mulyadi Mulyadi; Muthmainnah Mursidin (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
The research aims to analyze the factors of students' anxiety in speaking English. This research used a qualitative method with a purposive sampling technique, 20 students of class X were selected as participants. Data was obtained through interviews, observation checklists, and documentation. This research found that grade X students experienced speech anxiety factors. The results of the interviews found that speaking anxiety in students is caused by several factors including biological factors, negative thoughts, and emotional factors characterized by fear, trembling, worry in the form of negative feelings felt by individuals in communicating, usually in the form of feelings of tension, nervousness, or panic experienced by individuals in communicating with many people.